Amor e morte em Schopenhauer - Breda, Juliana Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
O presente projeto pretende analisar a função que os temas amor e morte exercem no conjunto da filosofia de Arthur Schopenhauer, examinando atentamente a evolução destes desde o início da construção de seu sistema filosófico. Procuraremos investigar em que medida o tema da morte pode ter servido de motivação, de gérmen à sua especulação filosófica, bem como seu entrelaçamento com o do amor, como impulso gerador da vida. Interessa-nos também o tratamento naturalístico e ético que Schopenhauer dá ao tema amor e morte: primeiramente ele empenha-se para dar uma imagem naturalista dos problemas tratados em Metafísica do Amor e Metafísica da Morte, mas logo ele torna claro que o problema é de ordem ética, contexto em que se apóia fortemente na literatura védica. Neste sentido, investigaremos também como Schopenahuer articula as Ciências Naturais e seus estudos dos Vedas

The present research project aims at analysing the role played by the themes „love“ and „death“ in the context of schopenhauerian philosophy as a whole, by means of a close investigation of the development of Schopenhauer’s refletions on both themes since the beginnings of his philosophycal efforts. We shall try to determine in what measure may the theme of death have worked as first motivation and as an “original seed” for his philosophical especulations, as well as this theme’s profound imbrication with that of love, understood as life generating impulse. We are also interrested in both the naturalistic and the ethical approaches presented by Schopenhauer reflections on love and death. On the one hand, he gives us a naturalistic account of the mentioned problems, but soon, in the other hand, he leaves it clear that these problems have also an ethical dimension. In his explorations of that dimension, his thinking appears to be heavily supported by vedic philosophy. Thus, we shall also investigate how does Schopenhauer menage to articulate nature sciences and his vedic studies
Keywords: Schopenhauer, Arthur, 1788 -1860; Amor; Morte; Ciencia